2003
DOI: 10.1177/000331970305400613
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Coronary Artery Dissection in a Woman Receiving 5-Fluorouracil

Abstract: A 39-year-old woman with cervical cancer treated with pelvic radiation therapy and 5-fluorouracil (5-FU) was hospitalized for dehydration and intractable vomiting. She developed an acute ST-elevation myocardial infarction (MI) that extended electrocardiographically after thrombolytic therapy. Coronary angiography demonstrated a completely occluded left anterior descending (LAD) artery with extensive coronary dissection that was treated successfully with stenting. The authors discuss several factors that may ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 11 publications
1
16
0
Order By: Relevance
“…Abbot et al (9) reported the case of a 39-year-old woman who presented with an ST segment elevation MI while undergoing 5-FU treatment for cervical cancer. Angiography demonstrated the presence of an extensive coronary artery dissection, which, the authors postulated, was at least partially the result of 5-FUprecipitated vasospasm and hormonal changes related to pelvic radiation (9). Similarly, cisplatin-induced coronary spasm, thrombogenesis and the altered hormonal milieu after the orchiectomy might have precipitated SCAD and the consequent myocardial infarction in our case.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Abbot et al (9) reported the case of a 39-year-old woman who presented with an ST segment elevation MI while undergoing 5-FU treatment for cervical cancer. Angiography demonstrated the presence of an extensive coronary artery dissection, which, the authors postulated, was at least partially the result of 5-FUprecipitated vasospasm and hormonal changes related to pelvic radiation (9). Similarly, cisplatin-induced coronary spasm, thrombogenesis and the altered hormonal milieu after the orchiectomy might have precipitated SCAD and the consequent myocardial infarction in our case.…”
Section: Discussionsupporting
confidence: 52%
“…In all of these reports, there was either no angiographic follow-up of patients who survived the acute event or follow-up angiography demonstrated complete healing of the dissection. The long-term outcome of the dissection that persists is less well described (9,10).…”
mentioning
confidence: 99%
“…Another retrospective examination of 377 case reports revealed acute MI in 22% of patients during 5-FU administration [6], while a prospective study of 26 patients suggested infarction by ECG and symptom criteria in nearly 35% of patients receiving 5-FU [1]. Coronary artery dissection causing an ACS has also been described with vasospasm--induced disruption of the endothelium cited as a possible mechanism of action [38].…”
Section: Silent Ischemia and Myocardial Infarctionmentioning
confidence: 99%
“…Patients with existing cardiovascular pathology have a high risk of this disease [10]. Some cases of myocardial infarction, sudden death and cardiac arrest associated with the capecitabine intake have been described [11,12].…”
Section: Discussionmentioning
confidence: 99%